Predicting sulphur dioxide dispersion isopleths from Multiple industrial sources in seberang perai using the Steady state gaussian plume model - Ahmad Hazmi, Nurul Suliana (2006)
Air quality modeling is an essential tool for most air pollution studies and the introduction of SO2 standards creates a need for modeling the dispersion of SO2. This work deals specifically with the use of the Steady State Gaussian Plume Model at Seberang Perai Industrial Area, Penang. The study utilized air quality data which span over a period of 5years (1999-2003). The first objective of this study was to simulate SO2 dispersion isopleths from multiple industrial sources at Seberang Perai Industrial Area which contributed to at least 70-75% of the total air pollution load in Penang. The second objective was to evaluate the Steady State Gaussian Plume Model by comparing the calculated and measured concentrations. The results showed that both simulated and measured concentrations are within a factor of 2, judged to be validated when the calculated and measured values do not differ in the annual averages by more than approximately 30% and the hourly concentration with 95% of the accumulative frequency distribution. Hence, Steady State Gaussian Plume Model employed by ISCST (design by the U.S EPA) is verified and is suitable for simulating air pollutants dispersion from industrial activities in this country. The dispersion isopleths obtained in this study confer the first dispersion isopleths in Seberang Perai and formed a basis study for future scenarios that include the impacts of increasing energy consumption per capita, of changing populations and of new industrial development, including their optimal siting.